ANALISIS KEBUTUHAN BAHASA INGGRIS JURUSAN TATA BOGA – PKK UNP PADANG - Al-Hafiz, Muhammad; Ratmanida, Ratmanida (Lingua Didaktika: Jurnal Bahasa dan Pembelajaran Bahasa, 2008)
People necessitate English is not only as a prestige, but it is a compulsory to be able to master English due to certain field. It can be noticed that today people need English for academic and job’s need level. This research reveals the correlation of English materials with academic and job’s need of students of Tata Boga UNP Padang. The correlation covers; English skills, provided topics, and the function of topics to support life skill of the graduates. For research’s execution, researchers use descriptive design. The populations are academic staffs, hotel and restaurant’ waiters/ress in Padang. The research finding shows that the those occupations in Padang need the workers who are able to master four integrated skills in English namely Listening, Speaking, reading, and writing. In fact the focus of English learning and teaching process at Tata Boga UNP is still limited on speaking.